Melanoma circulating tumor cells: Benefits and challenges required for clinical application. (28th June 2018) - Marsavela, G.; Aya-Bonilla, C.A.; Warkiani, M.E.; Gray, E.S.; Ziman, M.
Abstract: The implementation of novel therapeutic interventions has improved the survival rates of melanoma patients with metastatic disease. Nonetheless, only 33% of treated cases exhibit long term responses. Circulating tumor cell (CTC) measurements are currently of clinical value in breast, prostate and colorectal cancers. However, the clinical utility of melanoma CTCs (MelCTCs) is still unclear due to challenges that appear intrinsic to MelCTCs (i.e. rarity, heterogeneity) and a lack of standardization in their isolation, across research laboratories. Here, we review the latest developments, pinpoint the challenges in MelCTC isolation and address their potential role in melanoma management. Highlights: This review discusses Melanoma CTCs (MelCTCs). MelCTCs are promising liquid biopsy biomarkers in melanoma. They are heterogeneous with no common marker for their detection, unlike epithelial cancers. Label-independent methods are preferred for isolation of diverse MelCTCs. Identification of MelCTC subtypes provides significant clinical utility.